Inovasi Sistem Pengendalian Manajemen dalam Menghadapi Tantangan di Era Digital - Eri Kusnanto; Ngadi Permana; Sigit Pramono Hadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article discusses the importance of innovation in management control systems in the digital era. During the pandemic, significant shifts occurred in business, education, and public services, pushing organizations to adopt new technologies such as artificial intelligence (AI) and cloud computing to enhance efficiency and competitiveness. The article also addresses challenges companies face in managing cybersecurity risks, data privacy, and the need for robust regulations to protect personal information. Additionally, digital technologies like e-learning play a crucial role in facilitating the learning and personal development process, especially during the pandemic. Collaboration between sectors and nations is key to addressing these global challenges.